Lung Physiology and Obesity: Anesthetic Implications for Thoracic Procedures - Alessia Pedoto (Anesthesiology Research and Practice)
Obesity is a worldwide health problem affecting 34% of the American population. As a result, more patients requiring anesthesia for thoracic surgery will be overweight or obese. Changes in static and dynamic respiratory mechanics, upper airway anatomy, as well as multiple preoperative comorbidities and altered drug metabolism, characterize obese patients and affect the anesthetic plan at multiple levels. During the preoperative evaluation, patients should be assessed to identify who is at risk for difficult ventilation and intubation, and postoperative complications. The analgesia plan should be executed starting in the preoperative area, to increase the success of extubation at the end of the case and prevent reintubation. Intraoperative ventilatory settings should be customized to the changes in respiratory mechanics for the specific patient and procedure, to minimize the risk of lung damage. Several non invasive ventilatory modalities are available to increase the success rate of extubation at the end of the case and to prevent reintubation. The goal of this review is to evaluate the physiological and anatomical changes associated with obesity and how they affect the multiple components of the anesthetic management for thoracic procedures.